Flushing sand-laden manure - Harner, Joseph P.; Strahm, T.D.; Murphy, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sand can be handled successfully either in a scrape or flush system by developing handling systems that allow for the sand-laden manure to settle prior to the effluent entering a lagoon. The abrasiveness and density of sand create problems in handling the manure. Manure weighs about 60 lb/cu ft, whereas sand has a density of 120 lb/cu ft. Sand-laden manure will have an approximate density of 80 lb/cu ft, if 30% of the manure is sand. Because sand is heavier, it will not remain in suspension as long as manure and settles rapidly. Many problems associated with handling sand-laden manure can be avoided if the solids are stored separately from the effluent.
Keywords: Dairy; Flush; Sand; Manure; Bedding